Grade-level differences in the association between cumulative family risk factors and problematic smartphone use among Chinese adolescents - Ye Xu; Yi-fan Lin; Liwen Yang; Herui Wu; Wenjian Lai; Ruiying Chen; Subinuer Yiming; Zhiyao Xin; Wanxin Wang; Ciyong Lu (BMC Psychology)
Abstract Background Globally, more adolescents are engaged in problematic smartphone use (PSU), but there is scant research on the impact of family risk factors on PSU. This study aimed to investigate the independent and cumulative effects of various family risk factors on adolescents’ PSU and to determine whether these associations differ across grade level. Methods Data were drawn from the 2023 National School-based Chinese Adolescents Health Survey, with 20,361 adolescents (mean age: 15.0 [SD: 1.7] years) included. Family risk factors, PSU, and grade level were measured. A cumulative family risk (CFR) score was constructed by summing the number of family risk factors each adolescent experienced. The prevalence of PSU was estimated, and then logistic regression models were used to examine the association between family risk factors and PSU. Additionally, stratified analyses by grade level were conducted to explore differences in the above associations. Results The prevalence of PSU among adolescents was 25.8%. Significant associations were found between PSU and parental relationship, family function, parental education level, parental alcoholism, and childhood adversity, respectively. A clear dose–response relationship was observed between CFR and PSU (P for trend < 0.001), with adolescents exposed to four or more family risk factors showing the highest odds of PSU compared to those with no risk factors (OR: 2.57, 95% CI: 2.22–2.98). Furthermore, a significant interaction was found between CFR and grade level (P interaction <0.001), with middle school students showing a stronger association than high school students (P for ROR < 0.001). Conclusions Multiple family risk factors were independently and cumulatively associated with a higher risk of PSU, particularly among middle school students. These findings underscore the importance of addressing family-related risks and fostering emotionally supportive home environments to mitigate PSU in adolescents.